Globally Connected Fake Eyelash Industry in Relation to the Increase of Local Income per Capita (Case of Kutasari, Purbalingga Regency) - Galih Nur Seto; Isti Andini; Hakimatul Mukaromah (Desa-Kota: Jurnal Perencanaan Wilayah, Kota, dan Permukiman, 2024)
The impact of the global economy on foreign investment in various locations has a profound influence on the growth of local industries, including the fake eyelash industry, thereby stimulating local economic development. The emergence of local industries also brings about changes in the economic structure of local communities. This study aims to determine the extent to which local industries contribute to the rise in per capita income within these communities. To achieve this objective, the research initially identifies the characteristics of the industry and subsequently examines their impact on per capita income growth. The results demonstrate that the industry exhibits favorable conditions in terms of workforce, products, and relationships. Moreover, the industry has a high likelihood of positively influencing the increase in per capita income of local communities. In conclusion, local industries play a significant role in bolstering per capita income and even enhancing other aspects related to the community's quality of life.